Collembola Population Dynamics in Plants Organic Soybeans for Human Life - Chichi Josephine Manalu; Yusmaidar Sepriani (Budapest International Research and Critics University, 2022)
The diversity of soil organisms creates a variety of functions and processes in the soil. Each community of organisms performs different functions, among others, as nitrogen fixer, phosphate solubilizer, decomposer of organic matter, producer of phytohormones and antibiotics, and can be viewed as a soil ecosystem. Soil fauna plays a very big role in improving soil fertility. Soil fauna is classified as mesofauna, one of which is Collembola. Collembola is a group of microarthropods that has a wide distribution in various types of soil in the world. The role of Collembola in the soil is to destroy organic matter into smaller sizes and then mix them. Collembola is widely used as a biological indicator and ecosystem monitoring. The results showed that: The population of Collembola in organic soybeans had a value of 183 individuals/m2, Biomass of Collembola in organic soybeans had a value of 2.56 mg/m2, Collembola diversity in organic soybeans had a value of 0.89 (classified as low), Population, biomass and diversity of Collembola have a good impact on soil fertility, so it is a positive thing for people who cultivate, especially organic soybeans. Organic soybean cultivation is a good product for people, especially those who currently prioritize health.